Optimization of Drilling Parameters for Aluminum Metal Matrix Composite Using Entropy-Weighted TOPSIS under MQL Conditions - GHALME, Sachin G.; KAROLCZAK, Paweł (Engineering Transactions, 2023)
The aim of the present work is to understand the effect of drilling parameters (drill speed and feed rate) during the drilling of a Saffil fiber-reinforced Al metal matrix composite (MMC) under minimum quantity lubrication (MQL) condition. The effect of drilling parameters on individual response characteristics is evaluated and the optimum drilling parameters are also investigated using a multi-response optimization technique known as the entropy-weighted technique for order performance by similarity to ideal solution (EWTOPSIS). The drilling parameter optimization is performed with the aim of minimizing surface roughness in the drilled hole, roundness error in the drilled hole and feed force during drilling. The drilling parameters have a significant effect on individual responses. Weights were assigned to each response using the entropy weight method, and closeness coefficients were calculated to obtain the optimal level for the drilling parameters. A drill speed of 11 m/min and a feed rate of 0.05 mm/rev are the optimal combination to minimize the desired output responses simultaneously.